Kisah ‘Orang-Orang Angkat Pasir’ di Semenanjung Kepala Burung: Informalitas di Pinggiran Kota Sorong - Mahadika, Gilang; Pradana, Riki Ari (Jurnal HAM, 2025)
The term "mining" carries a sensitive connotation for the sand lifters on the margins of Sorong City, West Papua, who prefer to identify themselves as "orang-orang angkat pasir" (sand lifters). Their labor involves extracting sand from rivers and clearing hillsides—often through deforestation—to facilitate sand collection. The ecological repercussions of these informal sand mining activities, including deforestation, have drawn concern from local governments, residents, and environmental advocates, who view these practices as detrimental to the environment. This negative perception has contributed to the stigmatization of "sand mining" as a term and a practice. This paper examines the lives and livelihoods of sand lifters, addressing the question: How do they sustain themselves through sand mining activities? For many, sand lifting represents a last resort to survive and participate in urban development, even as their work contributes to environmental degradation. While sand mining poses significant ecological challenges, it simultaneously serves as a lifeline for marginalized communities striving to improve their living conditions. By focusing on the case of sand lifters in West Papua, this paper applies the concept of "infrapolitics" to explore the intersections of informality, political agency, and the right to livelihood in urban contexts. In doing so, it broadens the discourse on human rights, informality, and environmental justice in the region, highlighting on the complex dynamics between survival, urban development, and ecological impact.